The Impact of Poverty on Access to Healthcare Facilities Among Rural Households in Yobe State, Nigeria: A Sociological Assessment - Hussaini Ibn Mohammed (INTERNATIONAL JOURNAL OF MEDICAL EVALUATION AND PHYSICAL REPORT, 2026)
Access to healthcare remains a critical determinant of population health and social wellbeing. However, in many developing countries, including Nigeria, access to healthcare services is significantly constrained by socioeconomic inequalities, particularly poverty. This study examines the impact of poverty on access to healthcare facilities among rural households in Yobe State, Nigeria from a sociological perspective. The research explores how income level, education, employment status, and distance to healthcare facilities influence healthcare utilization among rural residents. A cross sectional survey design was adopted for the study. Data were collected from 250 rural households across selected communities in Yobe State using structured questionnaires. Descriptive statistics, correlation analysis, and logistic regression techniques were used for data analysis. The findings reveal that poverty significantly reduces access to healthcare services due to financial constraints, transportation difficulties, and inadequate healthcare infrastructure. Regression results indicate that household income, educational attainment, and distance to healthcare facilities are significant predictors of healthcare access. The study concludes that poverty remains a major structural barrier to healthcare utilization among rural households. It recommends improved rural healthcare infrastructure, expansion of health insurance coverage, and implementation of poverty reduction programs to improve healthcare access in rural communities.